The Economic Impact of International Tourism to Overcome the Unemployment and the Poverty in Indonesia - SUPRIYADI, Edy; KAUSAR, Devi Roza Krisnandhi (Journal of Environmental Management and Tourism, 2017)
The tourism sector has an important role in the Indonesia economy for the income resources, to create a job and to decrease the poverty. The research objective is to evaluate the factors impact of tourism Indonesia economy and give the government policy to overcome unemployment and poverty. He statements of problem in this research is to answer the current problem in Indonesia to decrease the number of unemployment and poverty through in increasing the tourist sector. Using the econometric model, the relationship among of the variables will have impact to other variable as unemployment, poverty when is given shock to any variable in tourist sector. The result research (1) the increasing consumption price index 10% will increase inbound tourist of Singapore, Australia is followed the expenditure and other impact increasing the poverty and unemployment, cost of hajj. (2) the increasing of the exchange rate 10 % will increase inbound tourist of Malaysia, Japan but decrease from Singapore and Australia and other impact increasing of cost of hajj. (3) the decreasing of rupiah the exchange 10% will increase inbound tourist of Singapore, Australia is followed the expenditure and other impact decreasing the poverty and unemployment. The conclusion is the variables CPI and Exchange rate will give the impact to inbound-tourist, unemployment and poverty which is important for the government’s policy.